Automatic continuous distraction osteogenesis device for hand reconstruction applications. (March 2022) - Hatefi, Shahrokh; Smith, Farouk; Abou-El-Hossein, Khaled
Highlights: Automatic continuous distraction osteogenesis techniques can be used in hand reconstruction applications. The conventional manual distraction osteogenesis methods for reconstruction applications in hand can be automated. By using automatic continuous techniques better results in shorter treatment period can be achieved. Abstract: Distraction Osteogenesis (DO) is an emerging technique for reconstruction of bone tissue in different body zones including mandible, tibia, hand, and foot. The application of DO technique in reconstruction of bone tissue has shown promising results compared to conventional reconstruction techniques, including bone grafting, prosthetics, and the vascularized flap. Mechanical distractors, with intermittent manual activation by the user, have been widely used in different reconstruction applications. Recently, automatic devices have been developed and used for enabling reconstruction applications using continuous DO technique. These devices can generate a continuous force while continuously moving the bone segment with high movement accuracy and distraction rate. In the continuous DO technique, by using a continuous force, instead of applying intermittent manual forces generated by the operator, better results in a shorter treatment could be obtained. Previous studies have shown that current automatic devices could positively influence bone tissue regeneration while obtaining promising results in the reconstruction of mandible. In hand reconstruction applications (HRA), only manual and mechanical mechanisms, using discontinuous DO technique, have been developed and used. In this research, an automatic device for HRA, using continuous DO technique, has been designed and developed. The proposed system is capable of generating a continuous distraction force for moving the bone segment in a fully automatic DO process. This novel reconstruction approach can be used for lengthening and reconstruction of different hand bones, including distal, middle, proximal, metacarpal, and carpal bones. In HRA, by using the proposed automatic continuous distractor better results in a shorter treatment period, compared to manual DO solutions, can be achieved